Partisipasi Masyarakat dalam pengelolaan kebersihan lingkungan melalui program Bank Sampah di Kelurahan Sukanagara - rahayu, widi (JPUS: Jurnal Pendidikan Untuk Semua, 2022)
Garbage is indeed a problem that always exists in people's lives, and is always looking for ways to anticipate or mitigate the negative impacts that it will cause. One of the breakthroughs is the waste bank which aims to change people's assumptions about waste and also make people aware to participate. The purpose of this study was to find out how the participation of the community in environmental hygiene management through the waste bank program. The research method used is a qualitative method with a descriptive approach through observation, interviews and documentation. The data analysis technique used is through four stages of data analysis which includes data collection, data reduction, data presentation and verification. The results showed that the community in Sukanagara Tanjungsari Village, Tasikmalaya City had participated in the implementation of the waste bank program in various stages, starting from the planning, implementation, enjoying the results and evaluation stages. The conclusion of this research is that the community participates in the stages of implementing the waste bank program for environmental hygiene management in Tanjungsari.